Enhancing multiclass brain tumor classification using deep learning: leveraging superior imaging representations to improve inferior modality performance - Hossain, Shah Md. Shakhawath; Alam, F M Tahoshin; Faiyaz, Hazra Mohammed Ahnaf (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.